2015
DOI: 10.1007/978-3-319-18173-8_23
|View full text |Cite
|
Sign up to set email alerts
|

Deciding the On-line Chromatic Number of a Graph with Pre-coloring Is PSPACE-Complete

Abstract: The problem of determining if the on-line chromatic number of a graph is less than or equal to k, given a pre-coloring, is shown to be PSPACE-complete. ⋆

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It remains open whether these problems are NP-complete, PSPACE-complete, or neither. In [16] it was shown that determining the online chromatic number is PSPACEcomplete if the graph is pre-colored and extended in [3] to hold even if the graph is not pre-colored.…”
Section: Complexity Of Determining the Online Independence Number Ver...mentioning
confidence: 99%
“…It remains open whether these problems are NP-complete, PSPACE-complete, or neither. In [16] it was shown that determining the online chromatic number is PSPACEcomplete if the graph is pre-colored and extended in [3] to hold even if the graph is not pre-colored.…”
Section: Complexity Of Determining the Online Independence Number Ver...mentioning
confidence: 99%
“…We call this decision problem Online Chromatic Number with Precoloring. The paper [13] conjectures that Online Chromatic Number (with no precolored part) is PSPACE-complete too. Interestingly, it is possible to decide χ O (G) ≤ 3 in polynomial time [7].…”
Section: Definition 2 the Online Chromatic Number Problem Is As Follmentioning
confidence: 99%
“…Inspired by [13], we prove the PSPACE-hardness of Online Chromatic Number by a reduction from Q3DNF-SAT, i.e., the satisfiability of a fully quantified formula in the 3-disjunctive normal form (3-DNF). An example of such a formula is…”
Section: Definition 2 the Online Chromatic Number Problem Is As Follmentioning
confidence: 99%
See 1 more Smart Citation